The Impact of Decent Work Practices, Employee Resilience and Psychological Contract Fulfillment on Work-life Balance in China's Banking Industry - Wu, Sitong; Nor Fairuz Syazana Binti Nor Fauzi (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
As competition in China's financial industry intensifies and employees' work pressure increases, employees' work-life balance issues have received more and more attention. Studies in China and other countries have shown that factors such as psychological contract fulfillment, employee resilience, and decent work practices are closely related to employees' work-life balance. Based on a literature review, this paper uses resource conservation theory and psychological contract theory to systematically analyze the relationship between the above independent variables and work-life balance, and proposes the hypothesis that psychological contract fulfillment, decent work practices, and employee resilience all have a positive impact on work-life balance. By simulating the survey data of Chinese banking employees and conducting regression analysis to verify, the results show that psychological contract fulfillment (β=0.235, p<0.001), decent work practices (β=0.382, p<0.001), and employee resilience (β=0.294, p<0.001) all have a significant positive impact on work-life balance, and the explanation rate of the regression model is 51.4%. These results are consistent with the conclusions of the literature, that is, meeting employees' psychological expectations, improving their resilience levels, and providing fair and safe working conditions are all conducive to improving the work-life balance of banking employees. Finally, the paper discusses the implications and limitations of the research and proposes suggestions for improvement.